A Scoping Analysis of Theories, Models, and Standard Operating Procedures for the COVID-19 Pandemic in Uganda - Semwogerere, Twaibu; Baker Kucel, Samuel; Igga, Huzairu; Lusiba, Badru; Gavamukulya, Yahaya; Namwanje, Sophie; Opaka Awichi, Richard; Matovu, Joseph; Barugahare, Banson John (International Journal of TROPICAL DISEASE & Health, 2022)
The Corona Virus Disease - 19 (COVID-19) pandemic is one of the most devastating events in the history of human health for the last several decades. Our analysis aimed at a cross-section of events, models and theories surrounding the pandemic. These included mathematical modeling, lockdown diaries, Standard Operating Procedures (SOPs), religious approaches, and the 5G network theory among others. The Global economies have been checked negatively by the pandemic. The COVID - 19 – pandemic challenge, primed many innovations and adaptations for survival. Use of phones and ICT as well as proper handling of asymptomatic victims was necessary as it resolves the anxiety issue of the infection spread. Leadership from the President to the lowers levels was critical for the management of COVID -19 challenge in Uganda.
Keywords: Theories; Models; Standard operating; COVID-19; Mathematical modeling